Knee height and knee height/height ratio of healthy schoolchildren - Annang Giri Moelyo; Andre Christiawan Susanto; Bella Monika Rajagukguk; Jonathan Billy Christian Tjiayadi (Paediatrica Indonesiana, 2020)
Background Knee height (KH) is rarely used to estimate stature in children, although its measurement might have benefit because not influenced by some musculoskeletal disorder in spinal region. Knee height and knee height/height ratio are typical in children due to different in pubertal timing of each child. Objective To derive a formula to estimate body height using knee height and to analyze the patterns of knee height and knee height/height ratio of healthy schoolchildren. Methods This cross-sectional study involved healthy children in one elementary school and one junior high school in Surakarta, Central Java. Demographic data were collected (sex, age, and ethnicity). All anthropometric measurements (height, weight, sitting height, and knee height) were taken three times, and their means were calculated. Linear regression analysis was used to compare height from knee height and sitting height. Non-parametric analysis through locally weighted scatterplot smoothing (LOWESS) was used to analyze the growth patterns of knee height, knee height/height ratio, and sitting height/height ratio. Results There were 633 children (328 boys and 305 girls) in this study. The formulas for the estimation of height were as follows: for boys, 2.40 × KH (cm) + 1.36 × age (years) + 20.31; and for girls, 2.48 × KH (cm) + 1.15 × age (years) + 19.58 (adjusted R2=0.97). Knee height increased earlier than sitting height in both boys and girls during childhood to adolescent period. Boys had a longer period of knee height increment than girls. Conclusion Knee height may be a useful alternative to estimate height in children. Knee height increases faster than height and sitting height in both boys and girls.